10 considerations for athlete selection: A resource and guide for researchers and practitioners - Johnston, K.; Roberts, A.; Baker, J. (Sports Coaching Review, 2025)
For good or bad, athlete selection remains a crucial step in the process of high-performance sport participation. Those in selector positions such as coaches, scouts, and senior administrators are responsible for making complex decisions regarding an athlete`s fit to a team, and that athlete`s future performance potential. These decisions ultimately shape the nature of the team or group, and directly influence an individual`s trajectory. Despite its importance, research regarding practices of athlete selection is relatively sparse, which presents a challenge for researchers and practitioners looking to make evidence-informed decisions. Knowing this, the present narrative review synthesises relevant articles focusing on athlete selection practices and theories (where available), and categorises current evidence in the form of "10 considerations for athlete selection". These considerations, while not exhaustive, serve as a guide for practitioners to reflect upon when making selection decisions. The paper concludes with a list of questions for practitioners to consider when they are performing athlete selections, which doubles as a list for researchers to expand upon from both a theoretical and empirical perspective.